Catalytic reactions within the cavity of coordination cages. (24th July 2019) - Fang, Yu; Powell, Joshua A.; Li, Errui; Wang, Qi; Perry, Zachary; Kirchon, Angelo; Yang, Xinyu; Xiao, Zhifeng; Zhu, Chengfeng; Zhang, Liangliang; Huang, Feihe; Zhou, Hong-Cai
Abstract : This review summarizes recent developments of coordination cages catalysis across three key approaches: (1) cavity promoted reactions, (2) embedding of active sites in the structure of the cage, and (3) encapsulation of catalysts within the cage. Abstract : Natural enzymes catalyze reactions in their substrate-binding cavities, exhibiting high specificity and efficiency. In an effort to mimic the structure and functionality of enzymes, discrete coordination cages were designed and synthesized. These self-assembled systems have a variety of confined cavities, which have been applied to accelerate conventional reactions, perform substrate-specific reactions, and manipulate regio- and enantio-selectivity. Many coordination cages or cage–catalyst composites have achieved unprecedented results, outperforming their counterparts in different catalytic reactions. This tutorial review summarizes recent developments of coordination cages across three key approaches to coordination cage catalysis: (1) cavity promoted reactions, (2) embedding of active sites in the structure of the cage, and (3) encapsulation of catalysts within the cage. Special emphasis of the review involves (1) introduction of the structure and property of the coordination cage, (2) discussion of the catalytic pathway mediated by the cage, (3) elucidation of the structure–property relationship between the cage and the designated reaction. This work will summarize the recent progress in supramolecular catalysis and attract more researchers to pursue cavity-promoted reactions using discrete coordination cages.